2012
DOI: 10.1007/s10384-012-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk factors for failure of trabeculectomy with mitomycin C after vitrectomy

Abstract: The prognostic factors for surgical failure of trabeculectomy with MMC in vitrectomized eyes are a higher preoperative IOP and NVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
(18 reference statements)
0
22
0
3
Order By: Relevance
“…We thus find it highly advisable to avoid disrupting conjunctival vessels when creating a 25-gauge sclerotomy in glaucomatous eyes that have undergone TLE. The prognostic factors for surgical failure of TLE with MMC in vitrectomized eyes have been reported to be high preoperative IOP and NVG [34]. As stated above, we had 3 NVG patients undergo additional TLE following 25GMIVS, and we were able to achieve a final reduction in IOP in all 3 eyes.…”
Section: Discussionmentioning
confidence: 86%
“…We thus find it highly advisable to avoid disrupting conjunctival vessels when creating a 25-gauge sclerotomy in glaucomatous eyes that have undergone TLE. The prognostic factors for surgical failure of TLE with MMC in vitrectomized eyes have been reported to be high preoperative IOP and NVG [34]. As stated above, we had 3 NVG patients undergo additional TLE following 25GMIVS, and we were able to achieve a final reduction in IOP in all 3 eyes.…”
Section: Discussionmentioning
confidence: 86%
“…Another study demonstrated that NVG eyes with a history of vitrectomy had poor surgical outcomes after trabeculectomy [22]. Vitrectomy exacerbates retinal ischemia and increases the concentration of inflammatory cytokines and/or VEGF in the anterior chamber [3].…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al reported the success rate of trabeculectomy with adjunctive Mitomycin-C to be 55.1% at 1 year, decreasing to 43.1% at 3 years. They proposed that high preoperative IOP and neovascular glaucoma are risk factors for failure [91]. Glaucoma drainage implant can be considered when there is a high risk of failure with trabeculectomy or in previously failed trabeculectomy.…”
Section: Glaucoma After Retinal Surgerymentioning
confidence: 99%